2000
DOI: 10.1212/wnl.55.8.1110
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome after surgery for epilepsy due to malformation of cortical development

Abstract: Surgery can offer seizure-free outcome for approximately one half of carefully selected patients with intractable focal epilepsy due to MCD. Complete resection of the MRI-apparent lesion may improve the likelihood for favorable outcome. MRI evidence of hemimegalencephaly or bilateral MCD suggests a low likelihood for postoperative freedom from seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
3
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 27 publications
10
68
3
5
Order By: Relevance
“…Using volumetric MRI data, extralesional volumetric abnormality of gray and subcortical matter has been demonstrated in patients with MCD and epilepsy, indicating the existence of extensive structural disorganization outside visually identified focal lesions (26). The fact that MCD were found in 10 of our 16 cases may explain why our results as to seizure freedom were inbetween the results of the limited number of reported cases of surgically treated MCD (25,27) and those reported in temporal lobe resections in general.…”
Section: Discussionmentioning
confidence: 54%
“…Using volumetric MRI data, extralesional volumetric abnormality of gray and subcortical matter has been demonstrated in patients with MCD and epilepsy, indicating the existence of extensive structural disorganization outside visually identified focal lesions (26). The fact that MCD were found in 10 of our 16 cases may explain why our results as to seizure freedom were inbetween the results of the limited number of reported cases of surgically treated MCD (25,27) and those reported in temporal lobe resections in general.…”
Section: Discussionmentioning
confidence: 54%
“…Identification of a focal epileptogenic lesion on preoperative MRI may affect postoperative seizure outcome favourably in both adult and paediatric patients, depending on location and pathology. [1][2][3][4][5][6][7][8][9] Similarly, other studies have shown a worse postoperative seizure outcome when no lesion has been found on MRI. [10][11][12][13][14][15][16][17] As MRI technology improves, smaller and more subtle lesions are being imaged and identified.…”
mentioning
confidence: 99%
“…3 22 23 Though published reports do not always give a detailed description of the localisation and extension of cortical dysplasia in children, the prominence of parietal and central localisation is described in studies by Chassoux et al, 14 and of multilobar lesions in studies by Hong et al 21 Other studies, on the other hand, have shown a frontal predominance 2 24 25 or a heterogeneous distribution. 5 In our survey, unilobar focal cortical dysplasias are located most often in the frontal lobe (four cases, including the two patients in whom MRI was negative), but the temporal lobe was involved in three cases, thus suggesting that this location could be relatively common in children. In fact, cases with temporal lobe involvement are reported more often in adults.…”
Section: Discussionmentioning
confidence: 71%